WOMEN, POLITICS AND DEVELOPMENT: THE ROLE OF EDUCATION - C., Izuagba A. (Sokoto Educational Review, 2020)
In Nigeria today women’s desire to actively participate in politics and occupy decision making positions has been limited greatly by gender bias that stems from our patriarchal system. Evidence from literature shows that in pre-colonial Nigeria women occupied decision making positions and were very visible in politics, unfortunately, the colonial m asters’ conception of women’s role in the society adversely affected the efforts made to empower women through education and policies. Not only is the content and process of education found to be gender biased, the constitution equally contain elements of gender bias which has made it very difficult to institutionalize some of the conventions that would have brought some leverage to Nigerian women. Based on these, the researcher recommends the restructuring of the education system in order to eliminate all forms of biases and gender inequity in order to ensure social justice and even development of the country.